THE SUBTLE SOCIAL AND EMOTIONAL NEEDS OF THE GIFTED - Irvin, Melanie (Acta Scientiae et Intellectus, 2024)
As the landscape in education is changing rapidly, gifted students’ unique needs are lacking appropriate attention to the social and emotional aspect. The social and emotional development of gifted students are neglected and in turn more problems arise for this population. The need for recognizing and acting upon the social and emotional needs of the gifted is in dire need. The phrase “it takes a village to raise a child” is a reminder for everyone to find better solutions to attend the social and emotional needs of the gifted and talented. The gifted students social and emotional needs are vital components for counselors, teachers, gifted coordinators, and parents to collaborate for the betterment of the child.